KERJASAMA TERNAK KAMBING PERSPEKTIF AKAD MUDARABAH DI DESA BEBEKAN SELATAN TAMAN SEPANJANG SIDOARJO - M. Muchlisin (Maliyah : Jurnal Hukum Bisnis Islam, 2014)
In the village of South Bebekan Throughout the park there are several activities Sidoarjo cooperation goats, made by the investors who provide capital in the form of money to the manager of the goats, while the manager is obliged to raise goats as well as possible, with forms of collaboration that has been agreed upon. Practice cooperation goats in the village of Sidoarjo Bebekan The Park South is a form of business cooperation between investors and goat livestock managers with profit sharing agreement with the parent who gave birth to a goat kid (andum bati or anvil) and profit sharing in the form of two young goats born (andum child), then owned by the management in the form of child benefit goats (kids andum) divided by the financier, became (andum bati). Contract analysis results of mud{a>rabah towards cooperation goats in the village of Sidoarjo Throughout Bebekan Park South, the practice of co-operation in the village Bebekan invalid because it does not fulfill the contract in harmony in mud{a>rabah, namely, lack of clarity in the division of profits, the manager impaired due to the profits subdivided property manager with the financiers.